2012
DOI: 10.1021/jp3074909
|View full text |Cite
|
Sign up to set email alerts
|

First Experimental Determination of the Absolute Gas-Phase Rate Coefficient for the Reaction of OH with 4-Hydroxy-2-Butanone (4H2B) at 294 K by Vapor Pressure Measurements of 4H2B

Abstract: The reaction of the OH radicals with 4-hydroxy-2-butanone was investigated in the gas phase using an absolute rate method at room temperature and over the pressure range 10-330 Torr in He and air as diluent gases. The rate coefficients were measured using pulsed laser photolysis (PLP) of H(2)O(2) to produce OH and laser induced fluorescence (LIF) to measure the OH temporal profile. An average value of (4.8 ± 1.2) × 10(-12) cm(3) molecule(-1) s(-1) was obtained. The OH quantum yield following the 266 nm pulsed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 30 publications
4
33
2
Order By: Relevance
“…First, it should be stressed that the maximum 4H2B concentration used in the present work (57 ppm) is significantly lower than the saturated vapor pressure at 297 K (1900 ppm). 22 Preliminary experiments showed that no significant loss (<1% per hour) of 4H2B, acetone, formaldehyde, acetic acid, and methanol was observed for at least 8 h in the dark. Tests for possible loss of products through photolysis were carried out.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
See 3 more Smart Citations
“…First, it should be stressed that the maximum 4H2B concentration used in the present work (57 ppm) is significantly lower than the saturated vapor pressure at 297 K (1900 ppm). 22 Preliminary experiments showed that no significant loss (<1% per hour) of 4H2B, acetone, formaldehyde, acetic acid, and methanol was observed for at least 8 h in the dark. Tests for possible loss of products through photolysis were carried out.…”
Section: ■ Experimental Sectionmentioning
confidence: 97%
“…The experimental setups and the data analysis are similar to those used in previous studies 17,22 and are thus only briefly described in the following. More details can also be found in previous publications.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…For larger hydroxycarbonyls (!C 4 ), degradation pathways have not been well characterized. The few available studies indicate that saturated hydroxyketones are mainly removed by OH radicals (Aschmann et al, 2000;Magneron et al, 2003;Messaadia et al, 2012;El Dib et al, 2013;Messaadia et al, 2013;Sleiman et al, 2013). Reactivity with O 3 and NO 3 radicals is expected to be not important in the atmosphere (Calvert et al, 2011).…”
Section: Introductionmentioning
confidence: 99%